2009
DOI: 10.1007/s00330-009-1463-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of hepatocellular carcinoma abutting the diaphragm and gastrointestinal tracts with the use of artificial ascites: safety and technical efficacy in 143 patients

Abstract: The purpose of this study was to assess the feasibility, safety and efficacy of radiofrequency ablation (RFA) with the use of artificial ascites for hepatocellular carcinoma (HCC) adjacent to the diaphragm and gastrointestinal tract. One hundred forty-three patients with 181 HCCs who underwent US-guided percutaneous RFA with the use of artificial ascites were retrospectively reviewed. Among the 181 HCCs, 148 HCCs were defined as problematic nodules for two major reasons: poor sonic window or possible thermal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 37 publications
(57 reference statements)
10
113
2
6
Order By: Relevance
“…Nevertheless, PEI is associated with a necrosis rate of 90%-100% in tumors < 2 cm and is still useful in selected patients when RFA is not technically feasible [40][41][42] . Recently, it was reported that in cases where the tumor is located under the diaphragm or near the surface of the liver, creating artificial ascites or pleural effusion is helpful in performing RFA and avoiding burns on adjacent organs [43,44] . This technique is being applied in several Asian countries with good results [43,44] .…”
Section: Interventional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, PEI is associated with a necrosis rate of 90%-100% in tumors < 2 cm and is still useful in selected patients when RFA is not technically feasible [40][41][42] . Recently, it was reported that in cases where the tumor is located under the diaphragm or near the surface of the liver, creating artificial ascites or pleural effusion is helpful in performing RFA and avoiding burns on adjacent organs [43,44] . This technique is being applied in several Asian countries with good results [43,44] .…”
Section: Interventional Therapiesmentioning
confidence: 99%
“…Recently, it was reported that in cases where the tumor is located under the diaphragm or near the surface of the liver, creating artificial ascites or pleural effusion is helpful in performing RFA and avoiding burns on adjacent organs [43,44] . This technique is being applied in several Asian countries with good results [43,44] . Several randomized controlled trials compared the efficacy of RFA with that of resection in Asian patients with HCC meeting the Milan criteria [45,46] .…”
Section: Interventional Therapiesmentioning
confidence: 99%
“…Another technique is creating a barrier between the liver and the colon, the hydrodissection. The use of 5% dextrose and saline solutions has been reported [14,28,39] . The former is preferred due to its properties since it does not conduct electricity and hence provides a thermal barrier around the organ [39] .…”
Section: Visceral Damagementioning
confidence: 99%
“…The use of 5% dextrose and saline solutions has been reported [14,28,39] . The former is preferred due to its properties since it does not conduct electricity and hence provides a thermal barrier around the organ [39] . Song et al [39] and Inoue et al [28] used artificial ascites and had no gastrointestinal injuries.…”
Section: Visceral Damagementioning
confidence: 99%
“…Adjacent visceral organs, such as small bowel or colon, can be displaced away from the tumor through patient positioning or hydrodissection (16). Hydrodissection can also be used to displace the diaphragm to prevent diaphragmatic injury during the ablation of tumors in the liver dome (17).…”
Section: Rf Ablation In Liver Tumorsmentioning
confidence: 99%